Sustainable Water Infrastructure Assessment of Raw Water Availability and Demand in a Nickel Mining-Impacted Watershed: A Case Study of the Pali River, East Halmahera, Indonesia - Hanie Teki Tjendani; Muliastuti; Sajiyo; Bambang Trigunarsyah; Buntara Sthenly Gan (International Journal of Hydrological and Environmental for Sustainability, 2026)
Rapid regional development, population growth, and land-use conversion associated with nickel mining have intensified pressure on raw water resources in many tropical watersheds. In mining-affected regions, the sustainability of water infrastructure depends not only on projected demand but also on the long-term reliability of raw water availability under low-flow conditions. This study assesses raw water availability, future clean water demand, and watershed protection requirements for the Pali River, the main gravity-fed raw water source for Maba City, East Halmahera, Indonesia. A quantitative hydrological approach was applied by integrating population projection, water demand estimation, watershed delineation, rainfall–runoff analysis using the F.J. Mock water balance model, and mining-induced catchment reduction scenarios. Water demand was projected to 2045, while dependable discharge was evaluated using Q90 low-flow reliability. The results show that the projected average clean water demand for Maba City reaches 36.19 L/s in 2045. Under the baseline non-mining condition, the Pali River watershed has an effective catchment area of 1.75 km² and a Q90 dependable discharge of 17.19 L/s. This value is already insufficient to meet the projected average demand under critical dry-season conditions. Mining-related catchment contraction further reduces the effective watershed area to 0.733 km² under Scenario 1 and 0.2973 km² under Scenario 2, decreasing dependable discharge to 7.20 L/s and 2.92 L/s, respectively. These findings indicate that the Pali River alone cannot provide a reliable long-term raw water supply for Maba City. Protection of the entire contributing watershed, development of alternative raw water sources, additional storage infrastructure, and continuous water quality monitoring are therefore essential to support sustainable water infrastructure planning in this nickel mining-impacted watershed.